Data warehousing design and advanced engineering applications methods for complex construction - Bellatreche, Ladjel 1968- (Advances in data warehousing and mining (ADWM), 2010)
This book covers the complete process of analyzing data to extract, transform, load, and manage the essential components of a data warehousing system. A defining collection of field discoveries, this advanced title provides significant industry solutions for those involved in this distinct research community